2011
DOI: 10.1007/s11738-011-0813-x
|View full text |Cite
|
Sign up to set email alerts
|

Roles of apoplastic peroxidases, laccases, and lignification in the manganese tolerance of hyperaccumulator Phytolacca americana

Abstract: We investigated the response of Mn-hyperaccumulator Phytolacca americana L. to manganese excess as well as the relationships between lignin deposition in the plant's leaves, peroxidase and laccase activities in the leaf apoplast, and Mn toxicity. The exceptionally high tolerance of P. americana to Mn, both in solution and in tissue, was confirmed. No visible brown spot was observed in the leaves of plants treated with B10,000 lM Mn for 10 days. Mn treatment significantly increased lignin content and laccase ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 61 publications
(82 reference statements)
1
11
0
Order By: Relevance
“…A laccase was shown to mediate broad-spectrum pathogen resistance in cotton by integrating the phenylpropanoid pathway, JA biosynthesis, and balance of JA-SA defense responses (Hu et al, 2018). In pokeweed, an increase in laccase activity during Mn treatment is thought to contribute to heavy metal tolerance by reducing the level of toxic reactive oxygen species (Gao et al, 2012). Also present in this cluster were fasciclin-like arabinogalactan proteins (FLAs).…”
Section: Discussionmentioning
confidence: 99%
“…A laccase was shown to mediate broad-spectrum pathogen resistance in cotton by integrating the phenylpropanoid pathway, JA biosynthesis, and balance of JA-SA defense responses (Hu et al, 2018). In pokeweed, an increase in laccase activity during Mn treatment is thought to contribute to heavy metal tolerance by reducing the level of toxic reactive oxygen species (Gao et al, 2012). Also present in this cluster were fasciclin-like arabinogalactan proteins (FLAs).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, ROS production and the lignification of cell walls are closely associated in plants. With the availability of H 2 O 2 as an oxidant, PODs generate monolignol phenoxy radicals that couple spontaneously to form lignin polymers (Gao, Peng, Chen, Wang, & Shen, ; Passardi, Penel, & Dunand, ). In this study, the plants in the high turbulence treatments exhibited high levels of lignin production compared with plants in mean flow and stagnant water.…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that Al can induce the expression of the enzyme genes in the lignin biosynthesis pathway, the expression of 4CL , CAD , C3H and PAL genes were increased under Al stress [ 100 ]. Other heavy metals such as copper (Cu), cadmium (Cd), zinc (Zn) and manganese (Mn) stress can also increase lignin content in some plants [ 76 , 96 , 101 , 102 , 103 , 104 ]. Increasing of Cu concentration in the culture medium enhanced the activity of PAL, CAD, caffeic acid POD, the accumulation of phenolic compounds and lignin in the suspension cells of ginseng root [ 105 ].…”
Section: Relationship Between Lignin Biosynthesis and Plant Stressmentioning
confidence: 99%
“…The results indicated lignin biosynthesis was crucial for the hyperaccumulation of Zn/Cd in Thlaspi caerulescens and it might be related to ion absorption and transport. Our previous study found that the deposition of lignin reduced the toxic effects of Mn, which is an important mechanism of manganese tolerance in a Mn-hyperaccumulator Phytolacca americana [ 101 ]. Lignification of xylem in roots can reduce the transport of Cd to the shoots [ 110 ].…”
Section: Relationship Between Lignin Biosynthesis and Plant Stressmentioning
confidence: 99%